2010
DOI: 10.1021/cb900248n
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Basis of Nitrogen Recovery through the Ureide Pathway: Formation and Hydrolysis ofS-Ureidoglycine in Plants and Bacteria

Abstract: While some organisms, including humans, eliminate oxidized purines to get rid of excess nitrogen, for many others the recovery of the purine ring nitrogen is vital. In the so-called ureide pathway, nitrogen is released as ammonia from allantoate through a series of reactions starting with allantoate amidohydrolase (AAH), a manganese-dependent enzyme found in plants and bacteria. We report NMR evidence that the true product of the AAH reaction is S-ureidoglycine, a nonstandard alpha-amino acid that spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…This finding implies that UGlyAH must be involved in vivo as well, because it has been shown that AAH will generate S-ureidoglycolate, the substrate of UAH, only in concert with UGlyAH (Serventi et al, 2010;Werner et al, 2010).…”
Section: Analysis Of Arabidopsis Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding implies that UGlyAH must be involved in vivo as well, because it has been shown that AAH will generate S-ureidoglycolate, the substrate of UAH, only in concert with UGlyAH (Serventi et al, 2010;Werner et al, 2010).…”
Section: Analysis Of Arabidopsis Mutantsmentioning
confidence: 99%
“…The corresponding mutants of Arabidopsis accumulate allantoate while showing a growth defect when allantoin is used as sole nitrogen source, demonstrating that AAH is essential for allantoate catabolism in this plant (Todd and Polacco, 2006;Werner et al, 2008). (2) Ureidoglycine aminohydrolase (UGlyAH), located in the ER, cleaves S-ureidoglycine hydrolytically to S-ureidoglycolate and ammonia in vitro (Serventi et al, 2010;Werner et al, 2010). Ureidoglycine is unstable and decays in the absence of an enzyme with a half-life of a few minutes to glyoxylate, ammonia, and urea (Fig.…”
mentioning
confidence: 99%
“…The occurrence of several pathways for the degradation of both allantoate and ureidoglycolate has been reported [16,17]. Most recent reports suggested that plants degrade allantoate to ureidoglycolate via allantoate amidohydrolase (AAH; EC 3.5.3.9) and ureidoglycine aminohydrolase (EC 3.5.3-) [18][19][20][21][22]. The ureidic plants relying upon N 2 fixation as the sole nitrogen source, ureides may comprise up to 86% of the N in the xylem sap, whereas amino acids, amides and nitrate are the major forms of nitrogen translocated from the roots after fertilization with nitrate [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of allantoate is hypothesized to involve its conversion to ureidoglycine by an allantoate amidohydrolase, HpxK (Serventi et al, 2009). The ureidoglycine aminotransferase HpxJ then converts the resulting ureidoglycine and an -keto acid to oxalurate and the corresponding amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting oxamate is then acted on by the putative oxamate Sequence analysis indicates that HpxW is a member of the -glutamyltranspeptidase (GGT) family. Most members of this family are involved in the cleavage of an -glutamyl amide linkage and transfer of the resulting -glutamyl group to other amino acids and peptides (Serventi et al, 2009). The GGT family is a member of the N-terminal nucleophile hydrolase (Ntn) superfamily, which has been well characterized (Brannigan et al, 1995;Oinonen & Rouvinen, 2000).…”
Section: Introductionmentioning
confidence: 99%